2013
DOI: 10.1007/s40368-013-0039-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of push-out bond strength of a new MTA-based sealer

Abstract: ProRoot MTA had the highest bond strength, whilst MTA Fillapex displayed the lowest values among the groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
4
17
1
1
Order By: Relevance
“…This is in agreement with previous research that also observed poor bond strength values for MTA Fillapex (16,22,23). This is a paste-to-paste sealer that, whenever mixed, establishes 2 important chemical reactions that are responsible for the material's setting and physical-mechanical characteristics, the progressive hydration of the orthosilicate ions and the reaction between MTA and salicylate resin (26).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with previous research that also observed poor bond strength values for MTA Fillapex (16,22,23). This is a paste-to-paste sealer that, whenever mixed, establishes 2 important chemical reactions that are responsible for the material's setting and physical-mechanical characteristics, the progressive hydration of the orthosilicate ions and the reaction between MTA and salicylate resin (26).…”
Section: Discussionsupporting
confidence: 92%
“…The use of endodontic sealers during root canal obturation yields the sealing between gutta-percha and dentinal walls, acting against bacterial leakage that may lead to endodontic failures (15,16). Every currently available root canal sealer presents limitations regarding the ideal properties of an endodontic sealer (17).…”
Section: Discussionmentioning
confidence: 99%
“…Results of our study also showed that MTA Fillapex had significantly lower bond strength than AH Plus and EndoSequence BC sealer. Similar results were obtained in a study by Sonmez et al [30] who compared the push-out bond strength of MTA Fillapex with ProRoot MTA and AH Plus. The results of this study are also in accordance with several recent studies which reported lower bond strength of MTA Fillapex in comparison to AH Plus.…”
Section: Section: Dentistrysupporting
confidence: 89%
“…This sealer is composed of salicylate resin, resin diluent, natural resin, bismuth oxide, silica nanoparticles, and MTA. Its physical properties (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) and biocompatibility (24,25) are already known. Nonetheless, to date, no studies have been conducted to analyze histologically the effect of MTA Fillapex in direct contact with bone tissue.…”
mentioning
confidence: 99%